Control of the modular multilevel matrix converter for wind energy conversion systems - Diaz, Matias (2017)
The nominal power of single Wind Energy Conversion Systems has been steadily growing, reaching power ratings close to 10 MW. In the power conversion stage, medium-voltage power converters are replacing the conventional low-voltage back-to-back topology. Modular Multilevel Converters have appeared as a promising solution for Multi-MW WECSs due to their characteristics such as modularity, reliability and the capability to reach high nominal voltages. Thereby, this thesis discusses the application of the Modular Multilevel Matrix Converter to drive Multi-MW Wind Energy Conversion Systems (WECSs).